Auditory-cognitive training for adult cochlear implant recipients: a study protocol for a randomised controlled trial - Blake J. Lawrence (BMC, 2021)
Abstract Background There is an urgent need to develop new therapies to improve cognitive function in adults following cochlear implant surgery. This study aims to determine if completing at-home computer-based brain training activities improve memory and thinking skills in adults following their first cochlear implant. Methods This study will be conducted as a single-blind, head-to-head, randomised controlled trial (RCT). It will determine whether auditory training combined with adaptive computerised cognitive training will elicit greater improvement in cognition, sound and speech perception, mood, and quality of life outcomes in adult cochlear implant recipients, when compared to auditory training combined with non-adaptive (i.e. placebo) computerised cognitive training. Participants 18 years or older who meet the clinical criteria for a cochlear implant will be recruited into the study. Results The results of this trial will clarify whether the auditory training combined with cognitive training will improve cognition, sound and speech perception, mood, and quality of life outcomes in adult cochlear implant recipients. Discussion We anticipate that our findings will have implications for clinical practice in the treatment of adult cochlear implant recipients. Trial registration Australian New Zealand Clinical Trials Registry ACTRN12619000609156 . Registered on April 23 2019.